Contrastive approach to the adaptation of Gender of French nouns in Italian and Croatian - Maslina Ljubičić (2003)
When we analyze the adaptation of gender of French nouns in Italian and Croatian, we find out that it represents a diverging component not only between the French model and a receiving language, but between the two receiving languages as well. In addition to the different morphophonological structure of Italian and Croatian, which is responsible for inconsistent results of the adaptation, other important factors are to be taken into consideration (intermediary languages, formal and semantic affinity). The failing coincidence of gender is one of the components of the grammatical divergence of otherwise the same Europeisms, therefore of grammatical false pairs.
Projekt MZOS
ENG